Microbiological testing in food safety management - Tompkin, R. B., ....-; ICMSF (New York : Springer, 2002)
Continuing this excellent series, "Microorganisms in Foods 7" describes the role of microbiological testing in modern food safety management systems. It explores how risk assessment and risk management can be used to establish goals - known as "tolerable levels of risk" or "food safety objectives" - for use in controlling foodborne illness, and provides guidelines for establishing effective management systems to control specific hazards in foods. It describes the respective roles of industry and government, recognizing that it is through their collective actions that effective food safety systems are developed and verified, and helps countries determine whether imported foods have been produced with an equivalent level of protection. This groundbreaking book will be of interest to food microbiologists, researchers, and others in the food industry, regulatory agencies and academia worldwide. The information has been prepared by the International Commission on Microbiological Specifications for Foods (ICMSF). The ICMSF was formed in response to the need for internationally acceptable and authoritative decisions on microbiological limits for foods moving in international commerce. Currently, the membership consists of eighteen food microbiologists from eleven countries, drawn from governmental laboratories in public health, agriculture, and food technology, from universities and from the food industry.
Keywords: Voedingsmiddelentechnologie